2016
DOI: 10.1101/gad.276287.115
|View full text |Cite
|
Sign up to set email alerts
|

Karyomegalic interstitial nephritis and DNA damage-induced polyploidy in Fan1 nuclease-defective knock-in mice

Abstract: The Fan1 endonuclease is required for repair of DNA interstrand cross-links (ICLs). Mutations in human Fan1 cause karyomegalic interstitial nephritis (KIN), but it is unclear whether defective ICL repair is responsible or whether Fan1 nuclease activity is relevant. We show that Fan1 nuclease-defective (Fan1 nd/nd ) mice develop a mild form of KIN. The karyomegalic nuclei from Fan1 nd/nd kidneys are polyploid, and fibroblasts from Fan1 nd/nd mice become polyploid upon ICL induction, suggesting that defective IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…Its efficient recruitment to mitomycin C (MMC)-induced DNA damage foci by ub-FANCD2 and the requirement of its UBZ domain in this process strongly implied a link between FAN1 and the FA pathway. However, this prediction was not substantiated by genetic data showing that FAN1 mutations segregate with KIN rather than with FA 10 12 . Moreover, FAN1-deficient cells are generally less sensitive to ICL-inducing agents than FA cells and, unlike FA cells, display no growth defects under normoxic conditions 7 .…”
Section: Introductionmentioning
confidence: 93%
“…Its efficient recruitment to mitomycin C (MMC)-induced DNA damage foci by ub-FANCD2 and the requirement of its UBZ domain in this process strongly implied a link between FAN1 and the FA pathway. However, this prediction was not substantiated by genetic data showing that FAN1 mutations segregate with KIN rather than with FA 10 12 . Moreover, FAN1-deficient cells are generally less sensitive to ICL-inducing agents than FA cells and, unlike FA cells, display no growth defects under normoxic conditions 7 .…”
Section: Introductionmentioning
confidence: 93%
“…It is possible that FAN1 may respond to a subset of ICLs that is somehow different in nature from the ICLs dealt with by the FA pathway. This might re ect a difference in the chemical nature of the ICLs or a difference in the genomic context of the ICLs recognized by the two pathways [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies suggested that the cross-link repair function of FAN1 is not within the FA pathway as: (i) homologs of FAN1 have been found in bacteria, archaea, and unicellular eukaryotes which lack FA proteins (19,(21)(22)(23), (ii) mutations in FAN1 do not cause FA, but instead a kidney disorder called karyomegalic interstitial nephritis (KIN) (24), (iii) N-terminal UBZ domain is dispensable for ICL repair, but is required for genomic maintenance, suggesting that the interaction of FAN1 with ID serves a function outside of ICL repair (25)(26)(27). Nevertheless, the sensitivity of FAN1-deficient cells to ICL-forming agents implicates FAN1 in ICL resolution independently of the FA pathway.…”
Section: Dna Synthesis (Tls) and The Second Strand Is Repaired By Hommentioning
confidence: 99%